Pleomorphic Adenoma in the Lower Lip: A Case Report and a Review - Nourwali, Ibrahim; Dar-Odeh, Najla (European Journal of Dentistry, 2019)
Pleomorphic adenoma constitutes 50% of salivary gland tumors affecting mostly the parotid gland extraorally, and the palate intraorally. While the upper lip is a common site, it is unusual to encounter this tumor in the lower lip. A 26-year-old man complained of a persistent lump affecting the lower lip. The lesion was excised and was shown on histopathological examination to be a pleomorphic adenoma with squamous metaplasia. At the 18-month review appointment, there was complete healing and no recurrence. Pleomorphic adenoma in the lower lip should be considered among the differential diagnosis of lower labial swellings, especially in young patients. There needs to be reconsideration of the epidemiological and histological characteristics.
Keywords: case report; lower lip; pleomorphic adenoma; salivary gland; squamous metaplasia